2021
DOI: 10.3390/cancers13092050
|View full text |Cite
|
Sign up to set email alerts
|

Influencers of the Decision to Undergo Contralateral Prophylactic Mastectomy among Women with Unilateral Breast Cancer

Abstract: (1) Background: The relatively high rate of contralateral prophylactic mastectomy (CPM) among women with early stage unilateral breast cancer (BC) has raised concerns. We sought to assess the influence of partners, physicians, and the media on the decision of women with unilateral BC to undergo CPM and identify clinicopathological variables associated with the decision to undergo CPM. (2) Patients and Methods: Women with stage 0 to III unilateral BC who underwent CPM between January 2010 and December 2017. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[7] In our study, nearly half of the visible calcifications on second-look US were associated with breast cancer. Given the independent predictive role of clinical manifestation in breast cancer and the strong recommendation for surgery in BI-RADS 5 calcifications, [5] improving the diagnostic accuracy of BI-RADS 4 calcifications without clinical manifestations and other abnormalities on MG could help avoid unnecessary interventional operations. Previous investigations have not revealed a correlation between color flow on second-look US and suspicious calcifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] In our study, nearly half of the visible calcifications on second-look US were associated with breast cancer. Given the independent predictive role of clinical manifestation in breast cancer and the strong recommendation for surgery in BI-RADS 5 calcifications, [5] improving the diagnostic accuracy of BI-RADS 4 calcifications without clinical manifestations and other abnormalities on MG could help avoid unnecessary interventional operations. Previous investigations have not revealed a correlation between color flow on second-look US and suspicious calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that clinical manifestations are significantly associated with breast cancer. [5] Therefore, we sought to investigate whether second-look US can assist in distinguishing BI-RADS 4 calcifications detected on MG without clinical manifestations or other abnormalities.…”
Section: Natural Science Foundation Of Fujian Province Of China (Gran...mentioning
confidence: 99%
See 1 more Smart Citation